Successful international experiences in childcare (Journal Of Educational and Psychological Researches, 2018)
The first few years of life is the basis for proper human personality and this Made by scientific studies and research need to make all efforts to achieve the early development of children and demonstrated by the efficiency and effectiveness of great success in the educational and developmental programs that have been applied to accelerate the children's growth rate in the various their sides, the current research aims to: identify the most successful international experience in the care and upbringing of children in early childhood has been determined by current research and previous studies manners within the cognitive perspective and dealing with the subject of this research and with respect to the theoretical framework Presented researcher theories that dealt with variable research interpretation and analysis of previous studies and achieve the goal of current research, the researcher to review what put the goal of research in the light of previous literature and then give a number of recommendations in the light of what has been achieved the goal of the research, the researcher recommended a number of recommendations are:1-recognition of teachers and officials of the essential role of parents in the education and upbringing and development of their children's education in every position.2-recognition of the central role already played by parents in early education for their children as well as their participation are continuing vital and inevitable to achieve learning successfully.